Obstetric and neonatal outcomes in women with pregnancy associated cancer: a population-based study in Lombardy, Northern Italy - Esposito, Giovanna (BMC Pregnancy Childbirth, 2021)
BACKGROUND: Pregnancy associated cancer (PAC) may lead to adverse obstetric and neonatal outcomes. This study aims to assess the association between PACs and adverse perinatal outcomes [i.e. labor induction, iatrogenic delivery, preterm birth, small for gestational age (SGA) newborn, low Apgar score, major malformations, perinatal mortality] in Lombardy, Northern Italy. METHODS: This population-based historic cohort study used the certificate of delivery assistance and the regional healthcare utilization databases of Lombardy Region to identify beneficiaries of National Health Service who delivered between 2008 and 2017. PACs were defined through oncological ICD-9-CM codes reported in the hospital discharge forms. Each woman with PAC was matched to four women randomly selected from those cancer-free (1:4). Log-binomial regression models were fitted to estimate crude and adjusted prevalence ratio (aPR) and the corresponding 95% confidence interval (CI) of each perinatal outcome among PAC and cancer-free women. RESULTS: Out of the 657,968 deliveries, 831 PACs were identified (1.26 per 1000). PAC diagnosed during pregnancy was positively associated with labor induction or planned delivery (aPR=1.80, 95% CI: 1.57–2.07), cesarean section (aPR=1.78, 95% CI: 1.49–2.11) and premature birth (aPR=6.34, 95% CI: 4.59–8.75). No association with obstetric outcomes was found among PAC diagnosed in the post-pregnancy. No association of PAC, neither during pregnancy nor in post-pregnancy was found for SGA (aPR=0.71, 95% CI: 0.36–1.35 and aPR=1.04, 95% CI: 0.78–1.39, respectively), but newborn among PAC women had a lower birth weight (p-value< 0.001). Newborns of women with PAC diagnosed during pregnancy had a higher risk of borderline significance of a low Apgar score (aPR=2.65, 95% CI: 0.96–7.33) as compared to cancer-free women. CONCLUSION: PAC, especially when diagnosed during pregnancy, is associated with iatrogenic preterm delivery, compromising some neonatal heath indicators. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12884-020-03508-4.